Taxonomy for multi-perspective assessment of the value of health information systems. (3rd December 2010) - Fitterer, Rene; Mettler, Tobias; Rohner, Peter; Winter, Robert
Healthcare-providing organisations realise astonishing advances in treatment procedures and medical technology that strongly impact health outcome. Despite recognition of potential contributions of Health Information Systems (HIS), their adoption is comparatively low. Based on the unified theory of acceptance and use of technology, six key variables are applied for a concept-driven literature research of criteria determining value of HIS. The resulting taxonomy contributes to the knowledge base a more detailed understanding of domain-specific HIS value indicators, which is tested for validity through a factor analysis.